A generalized Bartholdi zeta function for a general graph. Issue 5 (3rd May 2016) - Sato, Iwao; Mitsuhashi, Hideo; Morita, Hideaki
Abstract : We define an -variable Bartholdi zeta function and an -variable Bartholdi -function of a graph, and give determinant expressions of them. We present a decomposition formula for the -variable Bartholdi zeta function of a regular covering of . Furthermore, we express the -variable Bartholdi zeta function of a regular covering of G as a product of its -variable Bartholdi L -functions.